Role of mitochondrial quality control in neurodegenerative disease progression - Liu, Tingting; Sun, Weibo; Guo, Shuhao; Yuan, Zhiying; Zhu, Minghang; Lu, Jing; Chen, Tao; Qu, Yuanyuan; Feng, Chuwen; Yang, Tiansong (Frontiers in Cellular Neuroscience, 2025)
Neurodegenerative diseases are a diverse group of neurological disorders, in which abnormal mitochondrial function is closely associated with their development and progression. This has generated significant research interest in the field. The proper functioning of mitochondria relies on the dynamic regulation of the mitochondrial quality control system. Key processes such as mitochondrial biogenesis, mitophagy, and mitochondrial dynamics (division/fusion) are essential for maintaining this balance. These processes collectively govern mitochondrial function and homeostasis. Therefore, the mitochondrial quality control system plays a critical role in the onset and progression of neurodegenerative diseases. This article provides a concise overview of the molecular mechanisms involved in mitochondrial biogenesis, mitophagy, and mitochondrial dynamics, explores their interactions, and summarizes current research progress in understanding the mitochondrial quality control system in the context of neurodegenerative diseases.